IBON Philippines profile. (IBON Philippines Databank & Research Center, 1996)
"The handbook consists of 16 volumes with an average of 150 page per volume. Each volume discusses a certain region of the country. The selected data emphasize the rich potential but sorry state of our natural resources. They present the backwardness of our productive means and the extreme inequality in the control of properties and income. It has also provided data on government statistics on poverty, unemployment and social services infrastructure. The profiles also cover data on natural resources, people's socio-economic status, production, and social and economic infrastructure. The data is presented through tables and graphs."